Visual demands in modern Australian primary school classrooms. (17th February 2016) - Narayanasamy, Sumithira; Vincent, Stephen J; Sampson, Geoff P; Wood, Joanne M
Abstract: Background: The visual demands of modern classrooms are poorly understood yet are relevant in determining the levels of visual function required to perform optimally within this environment. Methods: Thirty‐three Year 5 and 6 classrooms from eight south‐east Queensland schools were included. Classroom activities undertaken during a full school day (9 am to 3 pm) were observed and a range of measurements recorded, including classroom environment (physical dimensions, illumination levels), text size and contrast of learning materials, habitual working distances (distance and estimated for near) and time spent performing various classroom tasks. These measures were used to calculate demand‐related minimum criteria for distance and near visual acuity, contrast and sustained use of accommodation and vergence. Results: The visual acuity demands for distance and near were 0.33 ± 0.13 and 0.72 ± 0.09 logMAR, respectively (using habitual viewing distances and smallest target sizes) or 0.33 ± 0.09 logMAR assuming a 2.5 times acuity reserve for sustained near tasks. The mean contrast levels of learning materials at distance and near were greater than 70 per cent. Near tasks (47 per cent) dominated the academic tasks performed in the classroom followed by distance (29 per cent), distance to near (15 per cent) and computer‐based (nine per cent). On average, children engaged in continuous near fixation for 23 ± 5 minutes at a time and during distance‐near tasks performed fixation changes 10 ± 1 times per minute. The mean estimated habitual near working distance was 23 ± 1 cm (4.38 ± 0.24 D accommodative demand) and the vergence demand was 0.86 ± 0.07 Δ at distance and 21.94 ± 1.09 Δ at near assuming an average pupillary distance of 56 mm. Conclusions: Relatively high levels of visual acuity, contrast demand and sustained accommodative‐convergence responses are required to meet the requirements of modern classroom environments. These findings provide an evidence base to inform prescribing guidelines and develop paediatric vision screening protocols and referral criteria.